2013
DOI: 10.3171/2013.5.jns1397
|View full text |Cite
|
Sign up to set email alerts
|

Management of simultaneous traumatic brain injury and aortic injury

Abstract: Object. Simultaneous traumatic brain injury (TBI) and aortic injury has been considered unsurvivable for many years because treatments such as sedation and blood pressure goals conflict for these 2 conditions. Additionally, surgical interventions for aortic injury often require full anticoagulation, which is contraindicated in patients with TBI. For these reasons, and due to the relative rarity of aortic injury/TBI, little data are available to guide treating physicians.Methods. A retrospective review was perf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 20 publications
0
7
0
Order By: Relevance
“…Byrnes et al 14 looked at therapeutic anticoagulation in patients with TBI and found that it can be safe; however, only two of the patients in that study were anticoagulated within 24 hours of their injury. Kitagawa et al 16 studied concurrent TBI and aortic injuries and found that six patients who received full anticoagulation intraoperatively during repair of their aortic injury had no progression of TBI; however, they did not report the time from injury in these patients.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…Byrnes et al 14 looked at therapeutic anticoagulation in patients with TBI and found that it can be safe; however, only two of the patients in that study were anticoagulated within 24 hours of their injury. Kitagawa et al 16 studied concurrent TBI and aortic injuries and found that six patients who received full anticoagulation intraoperatively during repair of their aortic injury had no progression of TBI; however, they did not report the time from injury in these patients.…”
Section: Discussionmentioning
confidence: 96%
“…As was noted earlier, there has been very limited literature about the early use of AT in patients with TBI. 14,16 Fortunately, the neurosurgeons at our institution have the same respect for BCVI as we do and allow for almost immediate initiation of AT in most patients, and this includes patients with an intracranial pressure monitor. A repeat head CT is performed if there is a neurologic examination change or once the aPTT reaches at least a therapeutic level to evaluate for worsening of the injury.…”
Section: Discussionmentioning
confidence: 96%
“…Furthermore, TBI patients can also harbor coexisting orthopedic, vascular, pulmonary, or hematological conditions that may also limit exercise capacity. [39][40][41][42][43] In this study, two treadmill tests were terminated by the treatment team. One test was terminated late in the study because of patient ataxia and imbalance secondary to previously known right-sided weakness.…”
Section: Discussionmentioning
confidence: 99%
“…It might be prudent to treat a lowgrade aortic injury with thoracic endovascular aortic repair (TEVAR), for example, if the non-operative management strategy runs counter to the optimal strategy for the management of a signifi cant non-aortic injury. Such might be the case in synchronous brain and aortic injury, where the goals of increasing cerebral perfusion pressure and decreasing aortic shear stress are likely to be diametrically opposed [37].…”
Section: Management Initial Managementmentioning
confidence: 99%
“…For patients with clinically threatening but stable aortic injuries (grade II-III injuries in the UT Houston paradigm, and moderate grade injuries in the University of Washington paradigm), TEVAR should be performed as soon as the signifi cant non-aortic injuries have been adequately stabilized [11,34]. Non-urgent repair of such aortic injuries will undoubtedly lead to rare cases of progression, rupture, and aortic-related mortality, but delayed repair in those cases will likely be dictated by an equally lethal burden of non-aortic injuries [37]. For patients able to tolerate delayed repair, the time interval may allow for the regression of intramural hematoma or intimal injuries, resulting in more stable endograft landing zones.…”
Section: Timing Of Repairmentioning
confidence: 99%